Stop Reaganism March and Rally Courthouse Park - Watkins, Howard::::::::: (1982)
Patience Milrod, Esther Padilla, Luisa Medina, and? Standing near Courthouse Water Fountain Devin Bleile-Kratzer and Adam Watkins in background